Two periodic solutions of neutral difference equations modelling physiological processes - Jun Wu; Yicheng Liu (Discrete Dynamics in Nature and Society)
We establish existence, multiplicity, and nonexistence of periodic solutions for a class of first-order neutral difference equations modelling physiological processes and conditions. Our approach is based on a fixed point theorem in cones as well as some analysis techniques.